MAGMA-INDUCED STRAIN LOCALIZATION IN CENTRIFUGE MODELS OF TRANSFER ZONES - Corti G.; Bonini M.; Mazzarini F.; Boccaletti M.; Innocenti F.; Manetti P.; Mulugeta G.; Sokoutis D. (My University, 2002)
Scaled centrifuge experiments have been used to investigate the dynamic relations between deformation and magma distribution in rift-related transfer zones. The physical models were built using suitable analogue materials, such as sand to represent the brittle upper crust, various kinds of silicone mixtures to simulate the lower crust and upper mantle and glycerol to reproduce magma. Models simulated the development of transfer zones across pre-existing glycerol reservoirs placed at the base of the analogue continental crust. In plan view, different geometries, dimensions and positions of subcrustal reservoirs were reproduced in three different sets of experiments; to compare results, models were also performed without magma-simulating glycerol.Set 1 experiments, incorporating a narrow rectangular glycerol reservoir, show that the low-viscosity material is able to localise deformation into the overlying crust, giving rise to discrete transfer zones. This concentrated surface deformation corresponds at depth to major magma accumulation. Set 2 experiments, with an initial wide squared glycerol reservoir, show instead that deformation is distributed across the whole model surface, corresponding at depth to relatively minor magma accumulation. Set 3 experiments explored various positions of a small squared reservoir that invariably localised faulting in the overlying analogue brittle crust at the onset of model deformation.The overall model behaviour suggests that magma distribution at depth can effectively control the strain distribution in the overlying crust and the deformative pattern of transfer zones. Strain distribution, in turn, may control magma emplacement as localized deformation would favour major accumulation of magma at transfer zones. Coupled to a strong thermal weakening of the country rocks, this process may ultimately lead to a positive feedback interaction between magma and deformation.
Keywords: TRANSFER ZONES; STRAIN LOCALISATION; MAGMA EMPLACEMENT; CENTRIFUGE MODELS